Advanced airway interventions for paediatric cardiac arrest: A systematic review and meta-analysis. (May 2019) - Lavonas, Eric J.; Ohshimo, Shinichiro; Nation, Kevin; Van de Voorde, Patrick; Nuthall, Gabrielle; Maconochie, Ian; Torabi, Nazi; Morrison, Laurie J.; ,; DeCaen, Allan; Atkins, Dianne; Bingham, Robert; et al.
Abstract: Aim: To assess the use of advanced airway interventions (tracheal intubation (TI) or supraglottic airway (SGA) placement), compared with bag mask ventilation (BMV) alone, for resuscitation of children in cardiac arrest. Methods: We searched Medline, EMBASE, and Cochrane Controlled Register of Trials (CENTRAL) for human trials and observational studies published before September 24, 2018 for clinical trials and observational studies with a comparison group. Two investigators reviewed studies for relevance, extracted data, and assessed risk of bias using the GRADE and CLARITY frameworks. Study authors were contacted when necessary to obtain additional data. Critically important outcomes included survival to hospital discharge and survival with good neurological outcome. Results: We identified 14 studies, including 1 pseudorandomised clinical trial, 3 observational cohort studies using propensity matching, and 8 simple cohort studies suitable for meta-analysis. The overall certainty of evidence was low to very low. For the critically important outcomes of survival to hospital discharge with good neurologic outcome and survival to hospital discharge results suggested better outcomes achieved with BMV than either TI or SGA; limited data favored SGA over TI. The majority of studies involved out-of-hospital cardiac arrest, with few studies of in-hospital cardiac arrest. Conclusions: TI or SGA are not superior to BMV for resuscitation of children in cardiac arrest, but the overall certainty of evidence is low to very low. Well designed randomised efficacy trials are needed to address this important question.